3m-2n-4=42

Simple and best practice solution for 3m-2n-4=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-2n-4=42 equation:


Simplifying
3m + -2n + -4 = 42

Reorder the terms:
-4 + 3m + -2n = 42

Solving
-4 + 3m + -2n = 42

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 3m + 4 + -2n = 42 + 4

Reorder the terms:
-4 + 4 + 3m + -2n = 42 + 4

Combine like terms: -4 + 4 = 0
0 + 3m + -2n = 42 + 4
3m + -2n = 42 + 4

Combine like terms: 42 + 4 = 46
3m + -2n = 46

Add '2n' to each side of the equation.
3m + -2n + 2n = 46 + 2n

Combine like terms: -2n + 2n = 0
3m + 0 = 46 + 2n
3m = 46 + 2n

Divide each side by '3'.
m = 15.33333333 + 0.6666666667n

Simplifying
m = 15.33333333 + 0.6666666667n

See similar equations:

| 4x+6=2.727272 | | 2x+22=3x+2 | | 11=18+7a | | x+20=34 | | 3(z+12)-7z+2=2(19-2z) | | 41/15=4/5r+2-1/2 | | 5x+4(-9x+17)=-27 | | 7y-1=2(y+3-2) | | 2-1(x-1)=13 | | -2(3x+9)+5(2x+3)=-39 | | 6x^2+3x-108=0 | | 2(w+3)-6w=-14 | | 2*6*3= | | =5*8 | | 5+3p=19 | | 4(5x+7)-(3-x)=4 | | 2n-n+5=3 | | 10+3-(8)= | | w+2x-3y+5y=-98 | | 30-9(5x+1)=-24 | | 5m=8-23m | | -(4a-8)=2(a+4) | | -30=-5x-15 | | x+4*3=x+18 | | 33%x+6=12 | | -4n+6=-3n+8+4 | | 30-9(5x+1)=24 | | 4x^2-32x+52=0 | | -8+x=11 | | -16x-15=14x-23 | | x=6+-15 | | 7x+8=3x+44 |

Equations solver categories